2010
DOI: 10.1073/pnas.0914065107
|View full text |Cite
|
Sign up to set email alerts
|

Calcium isotope constraints on the end-Permian mass extinction

Abstract: The end-Permian mass extinction horizon is marked by an abrupt shift in style of carbonate sedimentation and a negative excursion in the carbon isotope (δ 13 C) composition of carbonate minerals. Several extinction scenarios consistent with these observations have been put forward. Secular variation in the calcium isotope (δ 44∕40 Ca) composition of marine sediments provides a tool for distinguishing among these possibilities and thereby constraining the causes of mass extinction. Here we report δ 44∕40 Ca acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
164
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 216 publications
(187 citation statements)
references
References 65 publications
7
164
0
Order By: Relevance
“…This short term acidification event is not visible in our long-term δ 88/86 Sr sw record, but we anticipate that a negative excursion in δ 88/86 Sr sw , similar to that observed for Ca isotopes (Hinojosa et al, 2012;Payne et al, 2010), might be observed in future high resolution studies across the P/T boundary. Therefore, the predicted long term seawater anoxia is not necessarily in contradiction to the occurrence of a short term ocean acidification event on the order of a few hundred thousand years (Payne and Clapham, 2012;Sobolev et al, 2011).…”
Section: The Effect Of Changing Sea Level and Ocean Anoxia On The Marmentioning
confidence: 91%
See 1 more Smart Citation
“…This short term acidification event is not visible in our long-term δ 88/86 Sr sw record, but we anticipate that a negative excursion in δ 88/86 Sr sw , similar to that observed for Ca isotopes (Hinojosa et al, 2012;Payne et al, 2010), might be observed in future high resolution studies across the P/T boundary. Therefore, the predicted long term seawater anoxia is not necessarily in contradiction to the occurrence of a short term ocean acidification event on the order of a few hundred thousand years (Payne and Clapham, 2012;Sobolev et al, 2011).…”
Section: The Effect Of Changing Sea Level and Ocean Anoxia On The Marmentioning
confidence: 91%
“…Carbonate burial and dissolution are believed to have been closely linked to changes in seawater chemistry induced by ocean anoxia and acidification (Knoll et al, 1996;Payne et al, 2010;Riebesell et al, 1993;Woods et al, 1999). Massive weathering and recrystallization of continental carbonate shelves during sea level low stands could also contribute an additional flux of Sr to the ocean (Krabbenhöft et al, 2010;Stoll and Schrag, 1998).…”
Section: The Effect Of Changing Sea Level and Ocean Anoxia On The Marmentioning
confidence: 99%
“…An elevated oceanic carbonate inventory is a predicted aspect of an ocean without pelagic calcifiers, which only started proliferating during the Mesozoic and would effectively buffer short-term perturbations to P-Tr marine carbon isotopes (Kump and Arthur, 1999;Zeebe and Westbroek, 2003;Rampino and Caldeira, 2005;Ridgwell, 2005;Payne et al, 2010). This does not, however, exclude local departures from this dynamic equilibrium or depth-related isotope differences, such as those forced by the biological pump (Kump and Arthur, 1999;Rampino and Caldeira, 2005).…”
Section: Background: Permian-triassic Carbonate Carbon Isotope Recordsmentioning
confidence: 99%
“…The recognition and effects of acidification on the upper Permian marine biota have been suggested using the pattern of taxonomical selectivity, geochemistry of Calcium isotopes, dissolution and mineralogical composition of carbonates (e.g., Payne et al, 2007;Payne et al, 2010;Clapham and Payne, 2011;Hinojosa et al, 2012), but direct evidences on the fossil record are lacking.…”
Section: Seawater Acidificationmentioning
confidence: 99%